Pengembangan Multimedia Pembelajaran Interaktif Berbasis Android Menggunakan Smart Apps Creator (SAC) - Huzaima Mas'ud; Arip Mulyanto; Bait Syaiful Rijal; Muthia Muthia; Maemunah M (Jurnal Teknik, 2023)
The learning process today requires us to use various kinds of learning media to mediate various kinds of student learning styles, one of which is in terms of attracting students' interest in learning and improving learning outcomes. The purpose of this study is to see the advantages of SAC, especially the suitability of SAC to be used as a tool in the development of interactive multimedia learning, this research design will discuss the design of SAC for certain subject matter. In the development of this learning media using R&D research methods that have been modified according to the needs of media development. The results of this study concluded that from the aspect of the appearance of the learning media it was very interesting, the aspect of the content of the material was very feasible and the aspect of usefulness was very useful. The results of student assessment based on the display aspect get a percentage score of 53.3% or very interesting, student assessment based on the content aspect gets a percentage score of 56.7% or very feasible, while the usability aspect gets a percentage score of 56.7% or very useful.